Unraveling the Dynamics Between Advanced Technology, Logistics Customer Service, and Logistics Performance to Boost Customer Retention: Evidence from Shopee Express - Muhamad Faisal Nasrudin; Agus Purnomo; Melia Eka Lestiani (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2025)
Background: In a competitive logistics industry, companies face mounting pressure to meet customer expectations while maintaining operational efficiency. The adoption of advanced technology and enhanced logistics customer service has become essential for achieving timely delivery and customer satisfaction, directly influencing logistics performance and sustainable customer retention. However, empirical studies examining these factor interactions within West Java's logistics sector remain limited. Purpose: This study investigates the direct influence of Advanced Technology (AT) and Logistics Customer Service (LCS) on Customer Retention (CR) and examines the mediating role of Logistics Performance (LP). Method: This quantitative research employed a cross-sectional survey using structured questionnaires distributed to 385 Shopee Express customers in West Java through non-probability sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess both direct and indirect effects. Findings: The analysis reveals that both AT and LCS have a significant and positive impact on CR. LP partially mediates these relationships, highlighting that operational improvements reinforce direct effects of technological and service enhancements while serving as a critical pathway to strengthening customer loyalty. Conclusions: The study demonstrates that integrating advanced technological solutions with high-quality logistics customer service can significantly improve logistics performance, thereby strengthening customer retention. Research implication: Logistics providers in competitive e-commerce contexts should invest in digital innovations and robust service frameworks to secure a sustainable competitive advantage. Future research should employ longitudinal or mixed-methods designs with a broader geographic scope and explore additional factors, such as operational innovation and organizational culture.